Characterization of Somatic Mutations That Affect Neoantigens in Non-Small Cell Lung Cancer - Liang, Hongge; Xu, Yan; Chen, Minjiang; Zhao, Jing; Zhong, Wei; Liu, Xiaoyan; Gao, Xiaoxing; Li, Shanqing; Li, Ji; Guo, Chao; Jia, He; Wang, Mengzhao (Frontiers in Immunology, 2022)
Purpose: Immune checkpoint inhibitors (ICIs) have recent emerged as an important option for treating patients with advanced non-small cell lung cancer (NSCLC). Neoantigens are important biomarkers and potential immunotherapy targets, which play important roles in prognostication and treatments for patients with NSCLC. Therefore, this study aimed to evaluate and characterize the relationships between somatic mutations and potential neoantigens in specimens from patients who underwent surgical treatment of NSCLC. Patients and Methods: This prospective study evaluated specimens from patients with NSCLC who underwent surgical treatment at the Peking Union Medical College, China between June 2019 and September 2019. Whole exome sequencing was performed for the tumor tissues and corresponding normal tissues. Candidate neoantigens were predicted using generative software, and mutation characteristics were evaluated for relationships with the number of neoantigens. Results: Relative to mutations affecting all genes, neoantigen-related gene mutations were less frequent. Genes with a high neoantigen burden had more types and higher frequencies of mutations. The number of candidate neoantigens was positively correlated with missense mutations, code shift insertions/deletions, split-site variations, and nonsense mutations. However, only missense mutations were positively correlated with the number of neoantigens in the multiple linear regression analysis. The number of neoantigens was positively correlated with base transversions (A>C/C>A, T>G/G>T, and C>G/G>C) and negatively correlated with base transitions (A>G/G>A and C>T/T>C). Conclusion: The number of candidate neoantigens in NSCLC specimens was influenced by mutation frequency, type of mutation, and type of base substitution.